THE INFLUENCE OF LANGUAGE EDUCATION POLICY ON MULTICULTURAL EDUCATION - Dina Destari (Adisam Publisher, 2025)
Language education policies play an important role in establishing an inclusive education system and supporting cultural diversity. This research aims to analyze the influence of language education policies on multicultural education through a literature review approach (library research). This study examines various previous research and policies implemented in various countries in managing language education to support cultural diversity. The research results show that language education policies that support bilingualism and multilingualism contribute to increasing educational inclusivity, preserving cultural identity, and increasing accessibility and academic achievement of students from various backgrounds. Apart from that, effective implementation of language education policies also depends on the role of teachers, curriculum design that is responsive to diversity, and evidence-based policy support. However, challenges such as limited resources, social resistance, and the dominance of one language in the education system are still obstacles in implementing inclusive language education policies. This research provides recommendations for the government and educational institutions to develop more flexible and adaptive policies, by balancing the use of national languages, regional languages ​​and international languages ​​in education. Thus, language education policy can function as an effective tool in building a multicultural education system that is more inclusive, equal and just.